If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying W + -1 = 4w + 17 Reorder the terms: -1 + W = 4w + 17 Reorder the terms: -1 + W = 17 + 4w Solving -1 + W = 17 + 4w Solving for variable 'W'. Move all terms containing W to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + W = 17 + 1 + 4w Combine like terms: -1 + 1 = 0 0 + W = 17 + 1 + 4w W = 17 + 1 + 4w Combine like terms: 17 + 1 = 18 W = 18 + 4w Simplifying W = 18 + 4w
| 8-5x=1x+7 | | 1+2x-9=x | | 5x+2+5=11 | | x(x+30)=7000 | | 51-2x=6-7x | | y^2-x^2=-16 | | 21x^2-154x+168=0 | | 2x+7=-41-6x | | 8-5x=6x-9 | | 3(2x+3)=10 | | 14v^2+63v-35=0 | | 8m-2m=4 | | rad(15-x)+rad(3-x)=6 | | 8-5x=2x-3 | | 6x+11=3x+8 | | 15x+7x=11 | | (S^2-10s-11)= | | 8x^8+2x^4+9=0 | | y=150-x | | lg(2x-3)+1=0 | | P-8+1=-11 | | 7n^2+49n+42=0 | | 12x^4-7x^2+5=0 | | (S^2-16)= | | 25x^2=-60 | | 7(4-3x)=2(8x-9)+6 | | -4-2y=-30 | | 9x^2=-28 | | 3x-18=8x+6 | | 2x^2+56=0 | | (x-2)+(x+2)=252 | | 2x-(5+7x)=4-[x(2x+3)] |